Analysis of Equilibrium Concepts at Traditional Dance of Tari Banjarkemuning, Sidoarjo as an Innovation of Physics Learning by Ethnoscience Approach - Satria Putra, Achmad Maulana; Handayani,; Prihandono, Trapsilo; Bachtiar, Rayendra Wahyu (Universitas Negeri Surabaya, 2022)
Physics learning is rarely associated with local wisdom, so many people think the local arts have a separate topic from scientific study. This research analyzes the equilibrium concepts at Tari Banjarkemuning from Sidoarjo, East Java. This qualitative research uses content analysis techniques divided into six steps: unitizing, sampling, coding, reducing, inferring, and narrating. The data were collected by observation, documentation, and interviews. The research indicates that the equilibrium concept at Tari Banjarkemuning is the condition of equilibrium and the center of mass. The equilibrium state is shown in the motion of Embat-Embat and Solah Kembang Turi at the Sagah position (the silent moment of the dancers while inclined the bodies sideways and backward). Then, the center of mass is shown in the motion of Kejer (the dancers raise one leg) and Kencrongan (the dancers at the Tanjak position open- dancers’ legs perpendicularly at the knee). The integration of Tari Banjarkemuning in learning activities is expected for students to understand physics concepts easily. At the same time, it can make meaningful physics learning and build a better character for students.